The Locational choice of urban lifestyle migrants in Lisbon: beyond tourism imaginaries - McGarrigle, Jennifer (2021)
This chapter foregrounds discussions on the city as a lifestyle destination in the context of increasing urban tourism and privileged migration to the city of Lisbon. Drawing on qualitative data collected, between 2017 and early 2020, through life history interviews, this chapter aims to explore how intra-EU migrants benefiting from the Non-Habitual Residence (NHR) fiscal scheme understand and narrate their migration aspirations, motivations and locational choice. The desire to move is induced by past mobility experiences attending to the idea of migration as an ongoing transformative process. The structures of tourism are essential in creating a pre-migration imaginary of place and a mechanism in the decision-making process as movers travel to compare different locations refining place attributes conducive to their desired mode of life. Despite the tourism-induced nature of lifestyle migration to Lisbon, this chapter makes the case for analytical distinctiveness between tourism and lifestyle mobilities. Folding them together obscures the political asymmetries in the EU mobility regime and constellations of privilege reinforced by fiscal benefits. Moreover, in this case, the interpretative frames that migrants use to understand their mobilities dissociates them in ideological terms from tourists. The urban lifestyle prism reveals diverse lifestyle-led mobilities from retirees to working families in search of a lower-cost and slower urbanism and a better work-life balance supported by city infrastructures for consumption and continued production for the non-retired movers.